2009
DOI: 10.1542/peds.2009-1542g
|View full text |Cite
|
Sign up to set email alerts
|

Net Financial Gain or Loss From Vaccination in Pediatric Medical Practices

Abstract: We conclude that the vaccination portion of the business model for primary care pediatric practices that serve private-pay patients results in little or no profit from vaccine delivery. When losses from vaccinating publicly insured children are included, most practices lose money.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 16 publications
0
28
1
1
Order By: Relevance
“…Several recent studies of private pediatricians documented the potential for financial losses, from both vaccine purchase and vaccine administration, associated with providing vaccines to children and adolescents. [41][42][43][44] Concerns about reimbursement for vaccine purchase may be increasing as more-expensive vaccines are recommended for routine use. Two recent studies showed significant variation in both the prices private pediatric practices pay for identical vaccines and the insurance reimbursements they receive.…”
Section: Pressure On Private-sector Providersmentioning
confidence: 99%
See 3 more Smart Citations
“…Several recent studies of private pediatricians documented the potential for financial losses, from both vaccine purchase and vaccine administration, associated with providing vaccines to children and adolescents. [41][42][43][44] Concerns about reimbursement for vaccine purchase may be increasing as more-expensive vaccines are recommended for routine use. Two recent studies showed significant variation in both the prices private pediatric practices pay for identical vaccines and the insurance reimbursements they receive.…”
Section: Pressure On Private-sector Providersmentioning
confidence: 99%
“…Two recent studies showed significant variation in both the prices private pediatric practices pay for identical vaccines and the insurance reimbursements they receive. 41,42 Some practices are reimbursed more than the costs of the vaccines themselves, whereas others receive reimbursement that is less than they pay for vaccines; in 1 study, 21% of practices received less in reimbursement than their actual costs for purchasing a dose of varicella vaccine. 41 Some of the variability in vaccine purchase prices and reimbursements is likely attributable to suboptimal business practices in provider offices.…”
Section: Pressure On Private-sector Providersmentioning
confidence: 99%
See 2 more Smart Citations
“…41,42 Practices typically break even or gain small profits from vaccinations billed to commercial payers, whereas the opposite is true for those billed to Medicaid. 43 Because the modeled practice is a 50/50 payer mix, vaccines are excluded from both the FFS and capitation models.…”
Section: Expense and Revenues Under Ffs And Capitationmentioning
confidence: 99%